PENGUKURAN PENGARUH KINERJA PERUSAHAAN PADA PERUBAHAN HARGA SAHAM - Moechamad Nasir (Benefit: Jurnal Manajemen dan Bisnis, 2009)
This Research aim to know influence change of Current Ratio, Debt To Equity Ratio, Return On Investment, Return On Equity, Inventory Turn Over, Total of Asset Turn Over, and Earning to share price change either through together and or partial as well as to know change of finance ratio which having biggest influence to share price changeIn this research formulation of problem by researcher focused at what is change of Current Ratio, Debt To Equity Ratio, Return On Investment, Return On Equity, Inventory Turn Over, Total Asset Turn Over and Earning have influence to share price change, either through partial and or by together and from some the finance ratio, change of ratio which having biggest influence to share price change. The hypothesis is H1 : anticipated change of Current Ratio variable, Debt To Equity Ratio, Return On Investment, Return On Equity, Inventory Turn Over, Total Asset Turn Over and Earning have influence to Share price change by partial. H2 : anticipated change of Current Ratio variable, Debt To Equity Ratio, Return On Investment, Return On Equity, Inventory Turn Over, Total  Asset Turn Over and Earning have influence to Share price change by together. H3 : anticipated change of Earning variable represent variable having dominant influence to Share price change from other variable.The result of analysis show by using pooling data to analyses factor influencing KI Manufacture share price change in BEJ during period 2002 till 2005, with amount of n = 240, seen that PEPS variable, PITO, PTATO individually (evaluated from t value count) and is significant influence to share price change (PHS). Hereinafter PEPS variable represent most variable of significant influence share price change.